Incorporation of an acrylic fatty acid derivative as comonomer for oxidative cure in acrylic latex - Joana V. Barbosa (2014)
An acrylic fatty acid derivative (AcFAD) was evaluated as comonomer for promotion of oxidative cure in waterborne latexes. AcFAD was polymerized by solvent homopolymerization and copolymerization and by emulsion copolymerization, and the final products characterized. In the two polymerization processes, NMR analyses confirmed that the reaction occurred involving both the terminal acrylic double bond and the conjugated double bonds of the aliphatic chain. Compared with a reference acrylic latex, the results obtained after AcFAD incorporation showed a time-dependent increase in gel content and in solvent resistance of dry films. These were ascribed to oxidative cure and consequent self-crosslinking of the acrylic polymer, involving the conjugated double bonds in AcFAD side chains. Oxidative cure was also confirmed by FTIR analyses. In addition, reduction in minimum film-forming temperature evidenced that AcFAD has an internal plasticization effect during film formation. Incorporation of this comonomer in acrylic paint binder formulations constitutes a promising alternative to the use of volatile coalescing agents.